Impact of renewable energy utilization and artificial intelligence in achieving sustainable development goals. (November 2021) - Hannan, M.A.; Al-Shetwi, Ali Q; Ker, Pin Jern; Begum, R.A.; Mansor, M.; Rahman, S.A.; Dong, Z.Y.; Tiong, S.K.; Mahlia, T.M. Indra; Muttaqi, K.M.
Abstract: Many countries around the world are planning to reach 100% renewable energy use by 2050. In this context and due to the recent sharp increase in RE utilization in the global energy mix along with its progressive impact on the world energy sector, the evaluation and investigation of its effect on achieving sustainable development goals are not covered sufficiently. Moreover, an assessment of the emerging role of artificial intelligence for renewable energy utilization toward achieving SDGs is conducted. A total of 17 SDGs were divided into three groups, namely, environment, society, and economy, as per the three key pillars of sustainable development. Renewable energy has a positive impact toward achieving 75 targets across all sustainable development goals by using an expert elicitation method-based consensus. However, it may negatively affect the accomplishment of the 27 targets. In addition, artificial intelligence can help renewable energy enable the attainment of 42 out of 169 targets. However, with the current exponential growth of renewable energy share and artificial intelligence development and addressing certain present limitations, this impact may cover additional targets in the future. Nevertheless, recent research foci overlook essential aspects. The exponential growth of renewable energy share and rapid evolution of artificial intelligence need to be accompanied through the requisite regulatory insight and technology regulation to cover additional targets in the future. Highlights: Increment of global energy mix impact is not sufficiently covered in achieving SDGs. An emerging role of RE and artificial intelligence utilization toward achieving SDGs is assessed. Impact analysis of 17 SDGs is divided into environment, society and economy. Expert elicitation method is used for positive and negative impact analysis in achieving SDGs. Due to exponential growth, regulatory policy and technology is needed to cover all targets in future.